In situ capture of active species and oxidation mechanism of RhB and MB dyes over sunlight-driven Ag/Ag 3PO 4 plasmonic nanocatalyst - Teng, W.; Li, Xin Yong; Zhao, Q.; Zhao, J.; Zhang, D. (2012)
Sunlight-driven Ag/Ag 3PO 4 plasmonic nanocatalysts have been successfully prepared using an in situ ethylene glycol reduction method. The photocatalysts showed strong photocatalytic activity for decomposition of RhB and MB dyes under visible light irradiation (?>420nm). The excellent photocatalytic performance of Ag/Ag 3PO 4 came from the sensitivity of Ag 3PO 4 and the high separation efficiency of electron-hole pairs, which resulted in a large number of holes participating in the photocatalytic oxidation process. The results of density function theory calculation revealed that the visible-light absorption band in the Ag 3PO 4 catalyst is attributed to the band transition from the hybrid orbital of O 2p and Ag 4d to the Ag 5s and 5p orbital. The generation of active species in the photocatalytic system was evaluated using the fluorescence (FL) and electron spin resonance (ESR) techniques as well as in situ capture of active species by t-butanol and EDTA. The results indicated that the free hydroxyl radicals were not the major active oxidizing species in the photocatalytic process. The photocatalytic reaction process of the pollutants was mainly governed by the direct oxidation by the holes. © 2012 Elsevier B.V..